Bacopa monnieri (L.) Wettst. Extract Improves Memory Performance via Promotion of Neurogenesis in the Hippocampal Dentate Gyrus of Adolescent Mice - Hang Thi Nguyet Pham (International Journal of Molecular Sciences, 2020)
Bacopa monnieri L. Wettst. (BM) is a botanical component of Ayurvedic medicines and of dietary supplements used worldwide for cognitive health and function. We previously reported that administration of BM alcoholic extract (BME) prevents trimethyltin (TMT)-induced cognitive deficits and hippocampal cell damage and promotes TMT-induced hippocampal neurogenesis. In this study, we demonstrate that administration of BME improves spatial working memory in adolescent (5-week- old) healthy mice but not adult (8-week-old) mice. Moreover, improved spatial working memory was retained even at 4 weeks after terminating 1-week treatment of adolescent mice. One-week BME treatment of adolescent mice significantly enhanced hippocampal BrdU incorporation and expression of genes involved in neurogenesis determined by RNAseq analysis. Cell death, as detected by histochemistry, appeared not to be significant. A significant increase in neurogenesis was observed in the dentate gyrus region 4 weeks after terminating 1-week treatment of adolescent mice with BME. Bacopaside I, an active component of BME, promoted the proliferation of neural progenitor cells in vitro in a concentration-dependent manner via the facilitation of the Akt and ERK1/2 signaling. These results suggest that BME enhances spatial working memory in healthy adolescent mice by promoting hippocampal neurogenesis and that the effects of BME are due, in significant amounts, to bacopaside I.